Comparative study of conventional and magnetically coupled piezoelectric energy harvester to optimize output voltage and bandwidth - Ibrahim, Dauda Sh.; Abdul Muthalif, Asan Gani; Diyana, N. H.; Saleh, Tanveer (Springer Verlag, 2017)
Energy harvesting has experienced significant attention from researchers globally. This is due to the quest to power remote sensors and portable devices with power requirements of tens to hundreds of μW. Hence, ambient vibration energy has the potential to provide such power demands. Thus, cantilever beams with piezoelectric materials have been utilized to transduce mechanical energy in vibrating bodies to electrical energy. However, the challenge is to develop energy harvesters that can harvest sufficient amount of energy needed to power wireless sensor nodes at wide frequency bandwidth. In this article, piezo- electric energy harvester (PEH) beams with coupled mag- nets are proposed to address this issue. With macro fiber composite as the piezoelectric transducer, mathematical models of different system configurations having magnetic couplings are derived based on the continuum based model. Simulations of the system dynamics are done using numerical integration technique in MATLAB software to study the influence of magnetic interactions in generating power and frequency bandwidth due to base excitations at low frequency range. Experimental results comparing conventional system and the proposed piezoelectric beam configurations with coupled magnets are also presented. Finally, the optimal beam separation distance between the magnetic oscillator and PEH is presented in this work.